2012
DOI: 10.1016/j.chroma.2012.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography coupled to tandem mass spectrometry for the residue determination of ethylenethiourea (ETU) and propylenethiourea (PTU) in water

Abstract: Ethylenethiourea (ETU) and propylenethiourea (PTU) are the main degradation products of dithiocarbamates fungicides, which are widely used in agriculture from several years ago. Their determination in water at low concentrations (e.g. sub-ppb levels) is highly problematic due to their polar character and low molecular size. In the present study, two analytical methodologies have been developed and compared for the selective and sensitive determination of ETU and PTU in various types of waters. Both approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…It is interesting to notice that the ILIS 233 carbamazepine 10,11-epoxide-d 10 did not fully correct matrix effects for its own analyte. Similar 234 situation has been reported for some labelled compounds with a high degree of deuterated atoms 235 (Ripollés et al 2012). It seems that the isotope-labelled compound and the analyte had different 236 physico-chemical behaviour, leading to an (unexpected) unsatisfactory correction.…”
Section: Solid Phase Extraction Optimization 153mentioning
confidence: 66%
“…It is interesting to notice that the ILIS 233 carbamazepine 10,11-epoxide-d 10 did not fully correct matrix effects for its own analyte. Similar 234 situation has been reported for some labelled compounds with a high degree of deuterated atoms 235 (Ripollés et al 2012). It seems that the isotope-labelled compound and the analyte had different 236 physico-chemical behaviour, leading to an (unexpected) unsatisfactory correction.…”
Section: Solid Phase Extraction Optimization 153mentioning
confidence: 66%
“…This may lead to similar problems as with structural analoguesthe matrix compounds co-eluting with the sample are different resulting in different ionisation suppression. For example Ripolles et al 38 showed that propylenethiourea could not be determined with adequate recovery as the corresponding isotope-labelled (d 6 ) IS showed signicantly different chemical properties from the analyte (e.g. retention time, ionization behaviour).…”
Section: Accuracymentioning
confidence: 99%
“…The use of the own analyte ILIS is surely the best option for satisfactory correction in all sample types, but this assumption would need to be supported by experimental data as some labelled compounds (e.g. high degree of deuterated isotopes) can have different physico-chemical behavior than the analyte [26]. In multi-residue methods, it uses to be unpractical to correct each compound with its own ILIS due to the high cost and the low commercial availability of ILIS reference standards.…”
Section: Matrix Effect Studymentioning
confidence: 99%